Facile fabrication of lightweight carbon fiber/phenolic ablator with improved flexibility via natural rubber modification. (April 2022) - Song, Wenda; Jia, Xianfeng; Ma, Cheng; Wang, Jitong; Qiao, Wenming; Ling, Licheng
Abstract: The rigidity and low strain-to-failure of the phenolic impregnated carbon ablator seriously restrict the application of this state-of-the-art thermal protection material. In this study, to improve the flexibility of carbon fiber/phenolic ablator (CFPA), natural rubber (NR) was deposited homogeneously onto the surface of the carbon fibers through impregnation. Thus, a "bridge" was built between the carbon fiber reinforcement and the phenolic resin aerogel matrix, allowing the interface better connection and better deformation ability. Experimental results indicate that, compared with the unmodified, modified CFPA has lower flexural modulus and higher fracture strain, 6.3 MPa and 39.6% at the optimal NR latex mass fraction respectively, while maintains low density, good thermal insulation properties, and excellent ablation properties. The facile fabrication via natural rubber modification of CFPA improved its flexibility and could broaden the application scenarios of lightweight carbon/phenolic composite. Graphical abstract: Image 1 Highlights: A facile interfacial modification method was developed to fabricate flexible CFPA. NR is distributed on the interface of the composites and joints between fibers. NR improves the flexibility of CFPA while maintaining thermal protection properties.